Effect of Intrinsic Factors on the Incidence of Preterm Birth in Mothers with High-Risk Pregnancies - Rahmawati, Yessi; Wihastuti, Titin Andri; Hariyanti, Tita; Raharjo, Bambang (South Eastern European Journal of Public Health, 2024)
One of the problems caused by high-risk pregnancies is that babies are born preterm. Preterm birth is currently not known for sure, but it is thought to be triggered by a variety of mechanisms, including infection or inflammation, uteroplacental ischemic or bleeding, uterine overdistension, stress, and other immunological processes. Various factors are also associated with the occurrence of premature delivery, but the route of the mechanism is still being sought. The purpose of this study is to analyze the influence of intrinsic factors on the incidence of preterm birth in mothers with high-risk pregnancies at Waluyo Jati Hospital, Probolinggo Regency. This study is quantitative research with a cross-sectional approach. Sampling took place from January to June 2024 at Waluyo Jati Hospital, Probolinggo Regency. Sampling used the accidental sampling technique with a sample of 222 respondents who participated in this study. The results of this study showed that the most respondents with the criteria of the age range of 26-35 years were 103 respondents (46.4%), the last education was junior high school as many as 115 respondents (51.8%), the first pregnancy as many as 64 respondents (28.8%), never had an abortion as many as 183 respondents (82.4%), spontaneous childbirth as many as 114 respondents (51.4%), had a history of previous comorbidities as many as 139 respondents (62.6%), normal BMI as many as 94 respondents (42.3%), normal Hb levels were 168 respondents (75.7%), and preterm labor was 150 respondents (67.6%). The results of the double liner regression statistical test obtained a P-value of 0.000. The conclusion of this study is that there is an influence of intrinsic factors on the incidence of preterm birth in mothers with high-risk pregnancies at Waluyo Jati Hospital, Probolinggo Regency.